WEARABLE-DETECTED ATRIAL FIBRILLATION ALERTS: CLINICAL YIELD, PSYCHOLOGICAL BURDEN, EQUITY, AND HEALTH-SYSTEM CONSEQUENCES - A STRUCTURED REVIEW - Radoslaw Sciepuro; Dawid Cyls; Marta Czarnowska; Nina Czarnowska (International Journal of Innovative Technologies in Social Science, 2026)
Background: Consumer smartwatches and wearable electrocardiographic monitors have moved part of atrial fibrillation (AF) screening into continuous, patient-initiated surveillance. Objective: To evaluate wearable-enabled AF detection in relation to diagnostic yield, clinical outcomes, overdiagnosis, psychological effects, health care utilization, equity, and governance. Materials and Methods: PubMed/MEDLINE was searched, with supplementary citation and guideline tracking. Twenty-nine publications were included in a structured narrative synthesis. Results: Large consumer-device studies found that irregular-rhythm notifications were un-common, and subsequent AF confirmation varied with device type, timing, and baseline risk. Randomized screening trials generally increased AF detection and anticoagulant initiation, but most did not demonstrate reductions in stroke, mortality, or hospitalization. Supported monitor-ing programs usually did not increase anxiety, whereas observational studies of routine weara-ble use identified greater symptom preoccupation, treatment concern, clinician contact, and di-agnostic activity. Consumer ownership and digital capability may also reproduce existing ine-qualities in access. Conclusions: A photoplethysmographic alert should initiate risk assessment and electrocardiographic confirmation rather than be treated as a diagnosis or an indication for therapy. Clinical value is more likely when screening is targeted, follow-up responsibility is ex-plicit, communication reduces uncertainty, and programs evaluate patient-important outcomes, workload, and equity alongside detection yield.